Inverse modeling of past lead atmospheric deposition in South Greenland. (March 2015) - Massa, Charly; Monna, Fabrice; Bichet, Vincent; Gauthier, Émilie; Losno, Rémi; Richard, Hervé
Abstract: The aim of this study is to model atmospheric lead fluxes in two different paleoenvironmental records located in southern Greenland. Fifty five sediment samples collected from the Lake Igaliku sedimentary sequence were analyzed for lead and aluminum concentrations, and lead isotopic compositions. The second archive consists in a previously published dataset, obtained from a minerogenic peat deposit, located at Tasiusaq, 16 km northwest from Lake Igaliku. A flux model fitted to both dataset produces similar results, allowing past anthropogenic atmospheric deposition to be reconstructed. This original method can be easily adapted for other studies where natural inputs dominate over discrete anthropogenic inputs. Highlights: We provide a new paleoenvironmental record of lead concentrations and lead isotopic compositions from southern Greenland. The geological background is not favorable to the direct determination of anthropogenic fluxes. We used inverse modeling to estimate anthropogenic lead deposition through time. The model is validated by the coherence of the results obtained from two independent records.